2010
DOI: 10.5897/jmpr10.383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larvicidal properties of the latex of Euphorbia tirucalli L. (Euphorbiaceae) against larvae of Anopheles mosquitoes

Abstract: Malaria is the most important vector-borne disease in tropical and subtropical countries. Although, different control measures like use of insecticide-impregnated mosquito nets and curtains, chemotherapy and others are in place, so far, malaria eradication has proved impossible in affected areas. Therefore, any measure that attempts to fight the parasite or its vector (Anopheles spp.) would be of help. In this experiment, we assessed the efficacy of Euphorbia tirucalli latex both as a herbal mosquito remedy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…LD 50 is the amount of a material, given all at once, which causes the death of 50% (one half) of a group of test insects). Mwine et al (2010) examined larvicidal properties of Euphorbia tirucalli L. latex against larvae of Anopheles mosquitoes. Results showed that the latex made total mortality at the highest dilution used of 1:250 in 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…LD 50 is the amount of a material, given all at once, which causes the death of 50% (one half) of a group of test insects). Mwine et al (2010) examined larvicidal properties of Euphorbia tirucalli L. latex against larvae of Anopheles mosquitoes. Results showed that the latex made total mortality at the highest dilution used of 1:250 in 5 days.…”
Section: Discussionmentioning
confidence: 99%